The Effect of Tahfidz Learning Programme Participation on Learning Motivation and Islamic Religious Education Learning Achievement - Najmussaqibah, Najmussaqibah; Huda, Nuril (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
This study aims to examine the effect of santri participation in the tahfidz learning program on learning motivation and learning outcomes of Islamic Religious Education (PAI) at Rumah Tahfidz Zainal Muhibbin. The background of this study rests on the importance of integrating spiritual values in Islamic Education learning strategies that are not only cognitive, but also affective. This study used a quantitative approach with a correlational design. A sample of 60 students was purposively selected with the criteria of participating in the tahfidz program for at least one semester and having an odd semester PAI report card in the 2024/2025 school year. The instruments used include a Likert scale-based learning motivation questionnaire and PAI score documentation. The results of statistical analysis showed that there was a significant positive relationship between participation in the tahfidz program and learning motivation (r = 0.648; p < 0.05), as well as between participation in tahfidz and PAI learning outcomes (r = 0.611; p < 0.05). Simple regression analysis showed that the tahfidz program contributed 42% to the variation in learning motivation and 37.3% to PAI academic achievement. This finding indicates that participation in tahfidz not only builds religious character, but also has a real impact on students' academic performance. This study confirms the importance of tahfidz program as an integrative pedagogical and spiritual approach in Islamic education learning. It is recommended that Islamic educational institutions develop a curriculum that makes tahfidz as part of strengthening the quality of value-based learning.